2020
DOI: 10.1016/j.lrp.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral antecedents of coopetition: A synthesis and measurement scale

Abstract: This study taps into managers' perceptions of coopetition antecedents to better understand why firms adopt coopetition. By analyzing and synthesizing findings from systematic reviews of coopetition literature we integrate knowledge on coopetition antecedents. We develop and validate a scale measuring behavioral coopetition antecedents: strategic rationale and coopetition mindset. Based on a random sample of 368 Polish tourism firms, we run exploratory and confirmatory factor analyses to find that antecedents u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 103 publications
3
118
0
4
Order By: Relevance
“…Additionally, extant research has also overlooked the potential direct relationship between ambidextrous managers and coopetition. In fact, scholars call for (1) clarity on the managerial characteristics in ambidextrous relationships (Felício et al, 2019) and (2) empirical investigation into the nature of managers involved in coopetitive relationships (Czakon et al, 2019). As a response to these calls, our study proposes exploration and exploitation as the ambidextrous skills of managers that are essential to pursue coopetition.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, extant research has also overlooked the potential direct relationship between ambidextrous managers and coopetition. In fact, scholars call for (1) clarity on the managerial characteristics in ambidextrous relationships (Felício et al, 2019) and (2) empirical investigation into the nature of managers involved in coopetitive relationships (Czakon et al, 2019). As a response to these calls, our study proposes exploration and exploitation as the ambidextrous skills of managers that are essential to pursue coopetition.…”
Section: Introductionmentioning
confidence: 97%
“…Tourism is a network-based industry par excellence: namely, a domain in which interdependence is essential (Björk & Virtanen, 2005) and collaborative or cooperative practices between different socio-economic actors within a destination are crucial for creating tourism products, services and experiences, and fostering innovation (Bramwell & Sharman, 1999;Czakon et al, 2019;Kylänen & Mariani, 2014;Mariani, 2016;Mariani & Giorgio, 2017;Novelli et al, 2006). Furthermore, networks are at the heart of collective action.…”
Section: Literature Review 21 Network Science Approaches To the Studmentioning
confidence: 99%
“…Another attempt concerns the behavioral antecedents of coopetition (Czakon et al, 2019), but as suggested, it deals with managerial perceptions explaining why some firms engage in coopetition while others do not, and is not focused on outcomes.…”
Section: Coopetition: An Increasingly Rigorous and Relevant Theoreticmentioning
confidence: 99%